The Economic Impact of AI-Driven Carbon Emission Reduction Strategies in Large-Scale Industrial and Office Settings (Cuestiones de Fisioterapia, 2023)
The swift impacts of climate change have compelled corporations and extensive office and industrial establishments to pursue new strategies for diminishing carbon emissions while ensuring economic sustainability. In this context, Artificial Intelligence (AI) has emerged as a transformative technology, offering sophisticated capabilities for monitoring, predicting, and optimizing energy consumption within complex systems. This article examines the economic effects of AI-augmented carbon mitigation measures and presents a methodology that reconciles environmental sustainability with operational efficiency. The research underscores, through a critical analysis of recent empirical studies and practical implementations, that AI applications, such as predictive maintenance, smart energy management systems, intelligent HVAC control, and industrial process optimization, reduce emissions while enhancing cost-effectiveness and resource utilization. It also examines how green innovation, digital infrastructure, and legislative frameworks affect the scalability and economic rewards of AI-driven solutions. The results contribute to the ongoing discussion on sustainable digital transformation, offering strategic guidance for decision-makers seeking to integrate AI with decarbonization objectives and long-term economic outcomes.